INTENSITAS SERANGAN DAN FLUKTUASI POPULASI LALAT PENGOROK DAUN (Liriomyza sp.) PADA TANAMAN KACANG PANJANG DENGAN BEBERAPA TEKNIK PENGENDALIAN - Latifah, Lia; Afifah, Lutfi; Mustikasari, Fauzia; Irfan, Budi (Jurnal Ilmiah Hijau Cendekia, 2025)
Leafminer flies are pests of vegetable plants that attack the leaves in the larval stage by making white grooved burrows in the mesophyll of the leaves. These burrows can cause leaves to fall earlier than they should. Leafminer flies can attack long bean plants and other horticultural plants. This research aims to obtain pest control techniques that can reduce the intensity of leafminer fly attacks on long bean plants. The research method used was a single-factor Randomized Block Design (RBD) consisting of 4 treatments and 6 replications. The treatment consists of C (Control), CC (Combination Control), BC (Biointensive Control), and SC (Synthetic Control). The results of research using analysis of the Least Significant Difference test (LSD) with a 5% real level showed that BC treatment gave the lowest intensity of leafminer fly attacks of 6.25% - 14.58% with a total population ranging from 3 - 8 individuals followed by SC of 6.25% - 18.75% with a total population ranging from 4 - 9 individuals, CC of 6.25% - 20.83% with a total population ranging from 3 - 10 individuals, and C of 25.00% - 33.33 % with a total population ranging from 12 – 16 individuals. Biointensive control can be an alternative control to reduce the intensity of leafminer fly attacks.